Wnt4 is significantly upregulated during the early phases of cisplatin-induced acute kidney injury - He, Yi-Xin (Sci Rep, 2018)
Wnt4 is a secreted growth factor associated with renal tubulogenesis. Our previous studies identified that renal and urinary Wnt4 are upregulated following ischemia-reperfusion injury in mice, but the roles of Wnt4 in other forms of acute kidney injury (AKI) remain unclear. Here, we investigated the changes in Wnt4 expression using a cisplatin-induced AKI model. We found that renal and urinary Wnt4 expression increased as early as 12 hours, peaked at day 4 following cisplatin-induced AKI and was closely correlated with histopathological alterations. By contrast, the serum creatinine level was significantly elevated until day 3, indicating that Wnt4 is more sensitive to early tubular injury than serum creatinine. In addition, renal Wnt4 was co-stained with aquaporin-1 and thiazide-sensitive NaCl cotransporter, suggesting that Wnt4 can detect both proximal and distal tubular injuries. These data were further confirmed in a clinical study. Increased urinary Wnt4 expression was detected earlier than serum creatinine and eGFR in patients with contrast-induced AKI after vascular intervention. This study is the first to demonstrate that increased expression of renal and urinary Wnt4 can be detected earlier than serum creatinine after drug-induced AKI. In particular, urinary Wnt4 can potentially serve as a noninvasive biomarker for monitoring patients with tubular injury.